Anxieties of democracy Tocquevillean reflections on India and the United States - Chatterjee, Partha, 1947-; Katznelson, Ira. (New Delhi ; Oxford : Oxford University Press, 2012)
Offering a comparative analysis of democratic experience in India and the United States, this text covers diversified topics such as citizenship, religion, capitalism, equality and minorities.
Includes bibliographical references.
Description based on print version record.
Keywords: Democracy -- India; Democracy -- United States; India -- Politics and government; United States -- Politics and government; Comparative government